Behavioral Medicine in the COVID-19 Era: Dawn of the Golden Age. Issue 8 (3rd August 2020) - Ruiz, John M; Revenson, Tracey A
Abstract : The global COVID-19 pandemic and efforts to stem its transmission highlights the essential role of behavioral medicine in contemporary healthcare. As a result, the Annals of Behavioral Medicine instituted a COVID-19 rapid review process in mid-April to bring new knowledge to publication. This editorial describes the first two papers accepted through this mechanism and issues a broader call to recognize the human element in transmission and mitigation, and for behavioral medicine to play a central role in all phases of research, care, and public messaging.